Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Risks, resources, and refugia: Spatial overlap between yellow-eyed penguin foraging distribution and prey, commercial fisheries, and marine protected areas - Rachel P. Hickcox; Thomas Mattern; Melanie J. Young; Mariano Rodríguez-Recio; Yolanda van Heezik; Philip J. Seddon (Biological Conservation, 2023)

The role of conspecifics during pelagic foraging of Magellanic and benthic foraging of Gentoo penguins in the Beagle Channel, Argentina - Sabrina Harris; Klemens Pütz; Thomas Mattern; Gabriela Scioscia; Andrea Raya Rey (Marine Biology, 2023)

Staying close to home: Marine habitat selection by foraging yellow-eyed penguins using spatial distribution models - Rachel P. Hickcox; Thomas Mattern; Mariano Rodríguez-Recio; Melanie J. Young; Yolanda van Heezik; Philip J. Seddon (Frontiers in Marine Science, 2022)
Endangered yellow-eyed penguins ( Megadyptes antipodes ) are central-place, benthic-diving foragers that search for prey in the productive marine areas off the coast of the South Island, New Zealand. Like other seabirds, they target specific, reliable areas of high prey abundance, which are often associated with oceanographic characteristics such as bathymetry, seafloor sediment type, and sea surface temperature. Employing GPS tracking data collected between 2003 and 2021, we created species distribution models using maximum entropy modelling (Maxent) to determine foraging space use and habitat suitability for yellow-eyed penguins across their entire South Island range and within five distinct subpopulations: Banks Peninsula, North Otago, Otago Peninsula, the Catlins, and Stewart Island. We quantified the importance of environmental variables for predicting foraging site selection during and outside the breeding season. Significant regional variation existed in predicted probability of penguin presence, and proximity to the nearest breeding area was a key predictor of suitable foraging habitat. When distance was not included in the models, dissolved oxygen concentration was the most important predictor in the overall South Island model and the North Otago, Otago Peninsula, and the Catlins subpopulation models, whereas water current speed and mean monthly turbidity were most important in Banks Peninsula and Stewart Island subpopulation models, respectively. Dynamic variables related to prey availability were often the most important variables in model predictions of the habitat selection of yellow-eyed penguins. Visualisations and findings from this study, particularly of the observed interactions between penguins and their marine habitat, can be used to direct conservation and resources during marine spatial planning and species management.

Niche partitioning between coexisting gentoo Pygoscelis papua and Magellanic penguins Spheniscus magellanicus at Martillo Island, Argentina - Harris Sabrina; Scioscia Gabriela; Pütz Klemens; Mattern Thomas; Raya Rey Andrea (Marine Biology, 2020)

Shallow divers, deep waters and the rise of behavioural stochasticity - Xavier Meyer; Andrew J. J. MacIntosh; Andre Chiaradia; Akiko Kato; Thomas Mattern; Cédric Sueur; Yan Ropert-Coudert (Marine Biology, 2017)

Virulence determinants of the human pathogenic fungus A spergillus fumigatus protect against soil amoeba predation - Falk Hillmann; Silvia Novohradská; Derek J. Mattern; Tilmann Forberger; Thorsten Heinekamp; Martin Westermann; Thomas Winckler; Axel A. Brakhage (Environmental Microbiology, 2015)
Summary Filamentous fungi represent classical examples for environmentally acquired human pathogens whose major virulence mechanisms are likely to have emerged long before the appearance of innate immune systems. In natural habitats, amoeba predation could impose a major selection pressure towards the acquisition of virulence attributes. To test this hypothesis, we exploited the amoeba Dictyostelium discoideum to study its interaction with A spergillus fumigatus , two abundant soil inhabitants for which we found co‐occurrence in various sites. Fungal conidia were efficiently taken up by D . discoideum , but ingestion was higher when conidia were devoid of the green fungal spore pigment dihydroxynaphtalene melanin, in line with earlier results obtained for immune cells. Conidia were able to survive phagocytic processing, and intracellular germination was initiated only after several hours of co‐incubation which eventually led to a lethal disruption of the host cell. Besides phagocytic interactions, both amoeba and fungus secreted cross inhibitory factors which suppressed fungal growth or induced amoeba aggregation with subsequent cell lysis, respectively. On the fungal side, we identified gliotoxin as the major fungal factor killing D ictyostelium , supporting the idea that major virulence attributes, such as escape from phagocytosis and the secretion of mycotoxins are beneficial to escape from environmental predators.

Pollution, habitat loss, fishing, and climate change as critical threats to penguins - Phil N. Trathan; Pablo García‐Borboroglu; Dee Boersma; Charles‐André Bost; Robert J. M. Crawford; Glenn T. Crossin; Richard J. Cuthbert; Peter Dann; Lloyd Spencer Davis; Santiago De La Puente; Ursula Ellenberg; Heather J. Lynch; et al. (Conservation Biology, 2015)
Cumulative human impacts across the world's oceans are considerable. We therefore examined a single model taxonomic group, the penguins (Spheniscidae), to explore how marine species and communities might be at risk of decline or extinction in the southern hemisphere. We sought to determine the most important threats to penguins and to suggest means to mitigate these threats. Our review has relevance to other taxonomic groups in the southern hemisphere and in northern latitudes, where human impacts are greater. Our review was based on an expert assessment and literature review of all 18 penguin species; 49 scientists contributed to the process. For each penguin species, we considered their range and distribution, population trends, and main anthropogenic threats over the past approximately 250 years. These threats were harvesting adults for oil, skin, and feathers and as bait for crab and rock lobster fisheries; harvesting of eggs; terrestrial habitat degradation; marine pollution; fisheries bycatch and resource competition; environmental variability and climate change; and toxic algal poisoning and disease. Habitat loss, pollution, and fishing, all factors humans can readily mitigate, remain the primary threats for penguin species. Their future resilience to further climate change impacts will almost certainly depend on addressing current threats to existing habitat degradation on land and at sea. We suggest protection of breeding habitat, linked to the designation of appropriately scaled marine reserves, including in the High Seas, will be critical for the future conservation of penguins. However, large‐scale conservation zones are not always practical or politically feasible and other ecosystem‐based management methods that include spatial zoning, bycatch mitigation, and robust harvest control must be developed to maintain marine biodiversity and ensure that ecosystem functioning is maintained across a variety of scales. Contaminación, Pérdida de Hábitat, Pesca y Cambio Climático como Amenazas Críticas para los Pingüinos

Previous experiences with humans affect responses of Snares Penguins to experimental disturbance - Ursula Ellenberg; Thomas Mattern; David M. Houston; Lloyd S. Davis; Philip J. Seddon (Journal of Ornithology, 2012)

Diving behaviour of Little Penguins from four colonies across their whole distribution range: bathymetry affecting diving effort and fledging success - André Chiaradia; Yan Ropert-Coudert; Akiko Kato; Thomas Mattern; Julija Yorke (Marine Biology, 2007)

Protein expression profile of primary human squamous cell lung carcinomas indicative of the incidence of metastases - Manfred Volm; Reet Koomägi; Jürgen Mattern; Thomas Efferth (Clinical & Experimental Metastasis, 2002)